The Parents' Anxiety regarding Offline Schools during the COVID-19 Pandemic - Icha, Sitti Aisyah Nurramadhani Amran; Trisnawaty; Sakinah, Andi Irhamnia (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2024)
Anxiety emerged as one of the challenges during the COVID-19 pandemic. Based on information from the Republic of Indonesia Teachers Association, as many as 85% of parents feel anxious about their children's offline school readiness. This research aims to assess the relationship between offline school readiness and the level of anxiety experienced by parents during the COVID-19 pandemic. The research method used is a quantitative approach with a cross-sectional design. The research was carried out in the Aisyiyah Bustanul Athfal Kindergarten area, Mamajang District, involving the entire population as a sample. Of the total 81 respondents, 57% showed a low level of anxiety, while the majority of parents (53.5%) were ready to face the implementation of offline school for their children. Correlation analysis shows a p value of 0.216 (p < 0.05), which indicates that there is a very weak relationship between offline school readiness and the level of parental anxiety in Aisyiyah Bustanul Athfal Kindergarten, Mamajang District.